Behind Stereotype: The Relationship between Women and Violence - Huo, Shengyao (Transactions on Economics, Business and Management Research, 2024)
In people’s traditional impression, men are inherently violent and women are naturally peaceful. Liberal feminists argue that gender does not dictate one’s capacity for peace or violence; instead, societal factors play a crucial role. This article first expounds the reasons for the stereotype of women being naturally peaceful from the aspects of history and society. Secondly, it puts forward that women will also commit violence, and analyzes the scenes and reasons of women’s violence.